A single investor of the current account surplus? Benefits and risks of a monopoly supplier of money in Switzerland - Reto Foellmi (Aussenwirtschaft, 2017)
Studying the currency competition episode in Switzerland of the 19th century, I argue that modern economies need a single supplier of money to pursue stabilization policy. In small open economies with integrated capital markets, the uncertainty about the real exchange poses new risks to monetary policy which were only little discussed in the previous literature.
Keywords: 330